Hydrology and the management of watersheds - Brooks, Kenneth N.; Ffolliott, Peter F.; Magner, Joseph A.
Hydrology and the Management of Watersheds, Fourth Edition is a major revision and restructuring of this popular text. The content and scope have been improved and condensed, covering basic concepts and the fundamental aspects of hydrology and hydrologic processes, as well as methods and applications for managing watersheds. Examples throughout the book emphasize the use of web sites and access to the internet to acquire data, update methods and models, and to apply the latest technology to cope with issues of land and water use and climatic variability and change.Beyond the university classroom, Hydrology and the Management of Watersheds discusses land and water resource issues with implications for professionals in hydrology and watershed management in the United States